Transformasi Jaminan Kebendaan Menjadi Jaminan Tunai dalam Penjaminan Kredit Sindikasi Internasional - T. Murwadji (Fakultas Hukum Universitas Islam Indonesia, 2013)
This research studies: first, legal problem of Banking Guaranty Law in International Syndication Loan Collateral; second, mechanism of fixed collateral to cash collateral transmission which can be implemented in International Syndication Loan Collateral in Indonesia. Third, perspective of fixed collateral to cash collateral transformation in International Syndication Loan Collateral for the development of Civil Law in Indonesia. The method used was normative juridical using qualitative descriptive analysis method. The research findings conclude: First, the prevailing collateral law in Indonesia currently has not yet given assurance to the infrastructure project management to be trusted in channeling great amount of fund from International Loan Syndication. Second, Collateral Legal System in Indonesia is still unable to settle some problems, such as large amount of collateral value, small amount of collateral types which is not equal with the amount of loan limit, the relatively large value change of project, and loan execution involving other country’s legal system. Third, regulation perspective on the transformation and transmission of fixed collateral into cash collateral can be conducted in two alternatives.